ANTENA MIKROSTRIP BENTUK SEGIEMPAT - Surjati, Indra (Jurnal Teknik Elektro, 2001)
Patch antenna are popular for their well known attractive features, such as low profile,light weight and compatibility with monolithic microwave integrated circuits (MMIC) andmicrowave integrated circuits ( MIC ). There are many various shapes of patch antennas,such as rectangular, circular, square, triangular and ring. The simple shape isrectangular patch antenna and this paper will discuss about the rectangular patchantennaKeywords: feeding, coupling.